2019
DOI: 10.1021/acs.bioconjchem.9b00128
|View full text |Cite
|
Sign up to set email alerts
|

Surface Coordination of Black Phosphorus with Modified Cisplatin

Abstract: Black phosphorus (BP) is a two-dimensional (2D) nanomaterial with high charge-carrier mobility, a tunable direct bandgap, and a unique in-plane anisotropic structure; however, the easiness of BP oxidation into P x O y species in ambient conditions largely limits its applications. In this study, modified cisplatin−Pt−NO 3 [Pt-(NH 3 ) 2 (NO 3 ) 2 ] is used for surface coordination with BP nanosheets to generate Pt@BP, which maintains the surface morphology and properties of BP nanosheets for more than 24 h in am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Recently, Tofan et al have systematically studied the effect of a series of commercial group 13 Lewis acids on BP (Tofan et al, 2021). Also, they have reported that AlBr 3 Lewis acid could more effectively protect the few-layer BP from ambient degradation for at least 84 h and preserves transport properties of BP-based FETs for at least 72 h. Zhang et al proposed a cationic cisplatin species, Pt-(NH 3 ) 2 (NO 3 ) 2 , coordinated with the BP nanosheets obtaining Pt @ BP, which has showed stability for 10-day exposure to ambient conditions (Zhang et al, 2019a). The Pt @ BP has exhibited potential biomedical applications owing to its good cellular uptake rate and significant increment in the aspect of the drug sensitivity of cisplatin-resistant cancer cell lines compared with unmodified BP.…”
Section: Ion Modificationmentioning
confidence: 99%
“…Recently, Tofan et al have systematically studied the effect of a series of commercial group 13 Lewis acids on BP (Tofan et al, 2021). Also, they have reported that AlBr 3 Lewis acid could more effectively protect the few-layer BP from ambient degradation for at least 84 h and preserves transport properties of BP-based FETs for at least 72 h. Zhang et al proposed a cationic cisplatin species, Pt-(NH 3 ) 2 (NO 3 ) 2 , coordinated with the BP nanosheets obtaining Pt @ BP, which has showed stability for 10-day exposure to ambient conditions (Zhang et al, 2019a). The Pt @ BP has exhibited potential biomedical applications owing to its good cellular uptake rate and significant increment in the aspect of the drug sensitivity of cisplatin-resistant cancer cell lines compared with unmodified BP.…”
Section: Ion Modificationmentioning
confidence: 99%
“…Zhang et al prepared metal ion platinum (Pt)-modified bare BP through cation-π interaction to improve the stability of BP nanosheets ( Fig. 3 D–F) [ 77 ]. Wang et al customized the tripeptide Fmoc-Lys-Lys-Phe (Fmoc-KKF) for surface modification of BP nanosheets, and the modified BP@FKK complex not only had excellent stability, but also showed good cellular compatibility and enhanced cell uptake capacity [ 78 ].…”
Section: Biodegradability and Stability Of Bpmentioning
confidence: 99%
“…Reprinted with permissons from Ref. [ 77 ], Copyright 2019, Ameriacan Chemical Society. Abbreviations: RBCs, red blood cell; RMMVs, RM nanovesicles; aPD-1, cell death protein 1 antibody; MHC-1, major histocompatibility complex-1; DCs, dendritic cells; APCs, antigen presenting cells; CTL, cytotoxic Tlymphocyte.…”
Section: Biodegradability and Stability Of Bpmentioning
confidence: 99%
“…The lanthanide functionalization of BP not only prevents the oxidation in water and humid air but also enables them to be fluorescent and possess high R 1 relativities in magnetic resonance imaging (MRI). In a recent example, modified cisplatinPtNO 3 [Pt(NH 3 ) 2 (NO 3 ) 2 ] was used for the surface modification of BPNSs to generate Pt@BPNSs, which was then interacted with DNA both in vitro and in vivo . Compared with the unmodified cisplatin, the Pt@BPNSs showed a good cellular uptake rate and dramatically improved the drug sensitivity of cisplatin‐resistant cancer cell lines, holding great potential for applications in photothermal/chemotherapy.…”
Section: Covalent Functionalization On Bpnssmentioning
confidence: 99%